The development of confidence profiling for sport - Hays, K.; Thomas, O.; Butt, J.; Maynard, I. W. (The Sport Psychologist, 2010)
This study documents an ideographic approach to the assessment of sport confidence in applied settings. In contrast to traditional nomothetic measures, confidence profiling provides an assessment of sport confidence from the athlete`s own perspective. Seven athletes (4 male, 3 female) completed the profile and were encouraged to give an accurate account of their sources and types of confidence, and identify the factors that were debilitative to their confidence levels. Reflective practice on the application of confidence profiling, provided by three British Association of Sport and Exercise Science Accredited sport psychologists, demonstrated the versatility of approach, and indicated that the process allowed the athlete to accurately recall their confidence related experiences and attain an accurate and in-depth assessment of their sport confidence. Thus, it was concluded that completed confidence profiles could provide a strong foundation from which athlete-centered interventions might be developed.